2016
DOI: 10.1155/2016/9032809
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota as an Alternative Therapeutic Target for Epilepsy

Abstract: Epilepsy is one of the most widespread serious neurological disorders, and an aetiological explanation has not been fully identified. In recent decades, a growing body of evidence has highlighted the influential role of autoimmune mechanisms in the progression of epilepsy. The hygiene hypothesis draws people's attention to the association between gut microbes and the onset of multiple immune disorders. It is also believed that, in addition to influencing digestive system function, symbiotic microbiota can bidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Dysbiosis is seen in many pathologies, both locally, within the gastrointestinal tract, and systemically (59). While outside of the scope of this review, recent work has associated dysbiosis with obesity (60), metabolic diseases (61), cancer (62), neurological disfunctions (63), and many others, both in dogs and in humans. However, caution should be taken when interpreting those findings.…”
Section: Gut Microbiome In Diseasementioning
confidence: 99%
“…Dysbiosis is seen in many pathologies, both locally, within the gastrointestinal tract, and systemically (59). While outside of the scope of this review, recent work has associated dysbiosis with obesity (60), metabolic diseases (61), cancer (62), neurological disfunctions (63), and many others, both in dogs and in humans. However, caution should be taken when interpreting those findings.…”
Section: Gut Microbiome In Diseasementioning
confidence: 99%
“…The gut microbiota is also involved in the pathophysiology of behavior disorders, including drug addiction and substance abuse, while behavior modifications combined with microbiota regulation may have beneficial effects ( Engen et al, 2015 ; Vogtmann et al, 2015 ; Kiraly et al, 2016 ; Skosnik and Cortes-Briones, 2016 ). Additionally, the gut microbiota plays a vital role in the pathophysiology of neurobiological diseases, such as multiple sclerosis, hepatic encephalopathy, epilepsy, and migraine ( Liang et al, 2012 ; Sharon et al, 2016 ; Wu et al, 2016 ; Dai et al, 2017 ; van den Hoogen et al, 2017 ). The prevalence of mental disorders and neurological diseases has been ever increasing, almost in parallel with the changes in the human commensal microbiota.…”
Section: Gut Microbiota Gut-brain and Gut-brain Psychologymentioning
confidence: 99%
“…Several studies showed that diet posed a significant effect on GM[ 8 , 15 ]. A high-fat diet induced selective enrichment of bile-metabolizing microbiota, such as Bacteroides [ 16 ], whilst high-fiber foods promoted the accumulation of plant-polysaccharide fermenting microbial organisms, including Prevotella and Clostridium [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies declared that short-term dietary intake could rapidly alter human GM[ 8 , 15 ]. In this study, we performed a comparison between diseased infants (before and after KD treatment) and healthy controls, to explore if and how GM of infants with refractory epilepsy differed with that of age-matched healthy subjects.…”
Section: Introductionmentioning
confidence: 99%